Biological nutrient removal and recovery from solid and liquid livestock manure: Recent advance and perspective. (April 2020) - Zubair, Muhammad; Wang, Siqi; Zhang, Panyue; Ye, Junpei; Liang, Jinsong; Nabi, Mohammad; Zhou, Zeyan; Tao, Xue; Chen, Na; Sun, Kai; Xiao, Junhong; Cai, Yajing
Graphical abstract: Highlights: Application of composting with bulking agents was highlighted. Digestate from anaerobic digestion of solid manure as fertilizer was discussed. Biological nutrient removal and recovery from liquid manure was summarized. Economic sustainability and eco-environmental impacts were analyzed. Challenges and future prospects for nutrient removal and recovery were discussed. Abstract: Rapid development of livestock industry produces large amount of livestock manure rich in nutrients, organic matters, antibiotics, and heavy metals, thus imposes great harms to human and environment, if the manure is not suitably treated. Biological removal and recovery of nutrients from manure as agriculture fertilizer is attractive due to low cost and simple operation. This review offers an overview of recent development in biological nutrient removal and recovery from livestock manure. Livestock manure is divided into solid manure and liquid manure. Composting and anaerobic digestion of solid manure are fully discussed and important parameters are investigated. Then various processes of nutrient removal and recovery from liquid manure are summarized. Brief economic sustainability and eco-environmental effects are carried out. Finally, current challenges and future prospects in this field are analyzed.